Understanding the rise in traditional contraceptive methods use in Uttar Pradesh, India - Vasanthakumar Namasivayam; Bidyadhar Dehury; Ravi Prakash; Marissa Becker; Preeti Anand; Ashish Mishra; Shreya Singhal; Shivalingappa Halli; James Blanchard; Dean Spears; Shajy Isac (BMC, 2023)
Plain language summary In Uttar Pradesh, the use of traditional methods of contraception is on the rise, observed similarly in many other Indian states in recent times. The emphasis on modern contraceptive methods and the rise and high prevalence of traditional method use in the state call for a systematic assessment to understand the dynamics such as patterns, prevalence and reasons for traditional method use for better family planning programming. Using a state representative cross-sectional survey data from Uttar Pradesh, we attempted to understand the dynamics of increasing traditional methods use. We found no significant variations in use of traditional methods by their socio-demographic characteristics. Not only that, most current traditional method users reported that their first method was a traditional method and an overwhelming proportion of women (4/5 traditional methods users) expressed to continue with the same method in future. Also the findings reveal that more than half of the traditional method users used the method consistently over the three-years calendar period. Among those who had unmet need at the time of survey, a considerable proportion of them intend to use traditional methods in future. This emphasized the importance of initial contraceptive method choice on current contraceptive use and future preference. Traditional methods use increased in the state despite a significant increase (66.1 to 81.3% during 2018 to 2021) in availability of modern reversible methods and consistent availability of limiting method (84.0%) in public health facilities.